PPTTG Mesin Pencacah Serbaguna untuk Peternak Kambing di Dusun I Timur Karang Anyar - Kamil, Idham; Tarigan, Liwat; Siahaan, Kristianus BoBoby A.M.; Benar, Benar (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2022)
Dusun I Timur Karang Anyar Village Karang Anyar District Beringin Deli Serdang is one of the hamlets where goat breeders still use conventional methods in processing their feed. To provide feed for their goats, farmers have to grind elephant grass, cassava leaves and other forages that grow around the farm site or sometimes from nearby villages. This is quite energy and time consuming for the farmer. If the feed can be stocked for a long period of time, the effectiveness of the farmer's work will be higher. The purpose of this program is to apply appropriate technology to goat farmer groups in processing feed sources by mechanically processing through modernization of livestock with multipurpose animal feed chopping machines, increasing efficiency in the use of goat feed and time effectiveness for raising livestock. This service method is by making a chopping machine for goats that is tailored to the needs of partners and training partners on how to operate and maintain the chopper. With this activity, it is hoped that the efficiency of the use of animal feed and the effectiveness of maintenance time can be increased.